Profiling microRNA from nephrectomy and biopsy specimens: predictors of progression and survival in clear cell renal cell carcinoma. (18th May 2017) - Kowalik, Casey G.; Palmer, Drew A.; Sullivan, Travis B.; Teebagy, Patrick A.; Dugan, John M.; Libertino, John A.; Burks, Eric J.; Canes, David; Rieger‐Christ, Kimberly M.
Abstract : Objective: To identify microRNA (miRNA) characteristic of metastatic clear cell renal cell carcinoma (ccRCC) and those indicative of cancer‐specific survival (CSS) in nephrectomy and biopsy specimens. We also sought to determine if a miRNA panel could differentiate benign from ccRCC tissue. Materials and Methods: RNA was isolated from nephrectomy and kidney biopsy specimens ( n = 156 and n = 46, respectively). Samples were grouped: benign, non‐progressive, and progressive ccRCC. MiRNAs were profiled by microarray and validated by quantitative reverse transcription‐polymerase chain reaction. Biomarker signatures were developed to predict cancer status in nephrectomy and biopsy specimens. CSS was examined using Kaplan–Meier and Cox proportional hazards analyses. Results: Microarray analysis revealed 20 differentially expressed miRNAs comparing non‐progressive with progressive tumours. A biomarker signature validated in nephrectomy specimens had a sensitivity of 86.7% and a specificity of 92.9% for differentiating benign and ccRCC specimens. A second signature differentiated non‐progressive vs progressive ccRCC with a sensitivity of 93.8% and a specificity of 83.3%. These biomarkers also discriminated cancer status in biopsy specimens. Levels of miR‐10a‐5p, ‐10b‐5p, and ‐223‐3p were associated with CSS. Conclusion: This study identified miRNAs differentially expressed in ccRCC samples; as well as those correlating with CSS. Biomarkers identified in this study have the potential to identify patients who are likely to have progressive ccRCC, and although preliminary, these results may aid in differentiating aggressive and indolent ccRCC based on biopsy specimens.